2012
DOI: 10.1016/j.urology.2011.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Human Strains of Oxalobacter formigenes to Commonly Prescribed Antibiotics

Abstract: Objective To determine the sensitivity of 4 strains of Oxalobacter formigenes (OxF) found in humans, HC1, Va3, CC13, and OxK, to varying concentrations of commonly-prescribed antibiotics. OxF gut colonization has been associated with a decreased risk of forming recurrent calcium oxalate kidney stones. Methods For each strain and each antibiotic concentration, 100 μL of an overnight culture and 100 μL of the appropriate antibiotic were added to a 7 mL vial of oxalate culture media containing 20 mM oxalate. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 25 publications
0
35
1
1
Order By: Relevance
“…Studies to date suggest it occurs early in childhood (11), and if animal experiments provide any insight, it is obtained from the environment, not directly from the mother (12). Several studies have indicated that the intake of antibiotics can result in the loss of colonization (7,(13)(14)(15), and this is supported by decreased prevalence rates of O. formigenes in both cystic fibrosis patients (16) and calcium oxalate stone formers who are frequently prescribed antibiotics (15,17).Oxalate-degrading microbes are present in wild rodents (6,18,19) but are few or absent in laboratory rats (18,20) and laboratory mice (21). It is postulated that procedures used for establishment and maintenance of commercial rodent colonies limit the introduction and establishment of anaerobic specialist oxalate-degrading organisms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies to date suggest it occurs early in childhood (11), and if animal experiments provide any insight, it is obtained from the environment, not directly from the mother (12). Several studies have indicated that the intake of antibiotics can result in the loss of colonization (7,(13)(14)(15), and this is supported by decreased prevalence rates of O. formigenes in both cystic fibrosis patients (16) and calcium oxalate stone formers who are frequently prescribed antibiotics (15,17).Oxalate-degrading microbes are present in wild rodents (6,18,19) but are few or absent in laboratory rats (18,20) and laboratory mice (21). It is postulated that procedures used for establishment and maintenance of commercial rodent colonies limit the introduction and establishment of anaerobic specialist oxalate-degrading organisms.…”
mentioning
confidence: 99%
“…Studies to date suggest it occurs early in childhood (11), and if animal experiments provide any insight, it is obtained from the environment, not directly from the mother (12). Several studies have indicated that the intake of antibiotics can result in the loss of colonization (7,(13)(14)(15), and this is supported by decreased prevalence rates of O. formigenes in both cystic fibrosis patients (16) and calcium oxalate stone formers who are frequently prescribed antibiotics (15,17).…”
mentioning
confidence: 99%
“…This has particular relevance to pediatric urology given the frequency with which patients with anatomic abnormalities of the genitourinary system and recurrent infectionsare given prophylactic antibiotics. Oxalobacter has been shown to be resistant to amoxicillin, augmentin, ceftriaxone, and vancomycin [63], so it might be reasonable to consider using these antibiotics for prophylaxis where possible in order to avoid impacting O. formigenes colonization status, and ultimately, rates of stone formation. As Oxalobacter uses oxalate to meet both energy and carbon needs it has been suggested that low oxalate diets employed after a stone episode could impact colonization status [52].…”
Section: Urolithiasismentioning
confidence: 99%
“…For example, Oxalobacter formigenes is sensitive to commonly prescribed antibiotics [54] and vanishes after antibiotic treatment [55]. Since O. formigenes degrades oxalate, people who lose this microbe are hypothetically at increasing risk of kidney stone disease or hyperoxaluria [56].…”
Section: Antibiotics and Gut Biodiversitymentioning
confidence: 99%